Simplify.
(3a – 4)2

Question

Asked 11/21/2014 11:26:39 AM

Updated 11/21/2014 12:07:53 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

s

bcous05|Points 52|

Question

Asked 11/21/2014 11:26:39 AM

Updated 11/21/2014 12:07:53 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Rating

8

(3a – 4)^2

= (3a – 4)(3a – 4)

= 9a^2 - 12a - 12a + 16;

= 9a^2 - 24a + 16

= (3a – 4)(3a – 4)

= 9a^2 - 12a - 12a + 16;

= 9a^2 - 24a + 16

Added 11/21/2014 12:07:14 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/21/2014 12:10:34 PM]

Factor completely: 3x2 – 24x + 36

Question

Updated 11/22/2014 3:33:26 AM

1 Answer/Comment

3x^2 – 24x + 36

= 3(x^2 - 8x + 12)

= 3(x - 2)(x - 6)

= 3(x^2 - 8x + 12)

= 3(x - 2)(x - 6)

Added 11/22/2014 3:33:26 AM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [11/22/2014 10:38:13 AM]

Factor completely: 3x2 – 24x + 36 **Weegy:** 3x^2 – 24x + 36 = 3(x^2 - 8x + 12) = 3(x - 6)(x - 2) (More)

Question

Expert Answered

Updated 11/24/2014 1:44:14 PM

0 Answers/Comments

Simplify.
(3a – 4)2 **Weegy:** how may I help you? **User:** Simplify.
(3a – 4)^2
A.
9a2 – 16
B.
9a2 – 24a + 16
C.
6a2– 24a + 8
D.
92a – 7 + 16
(More)

Question

Not Answered

Updated 11/21/2014 7:24:44 PM

1 Answer/Comment

(3a – 4)^2

= 3a*3a - 2*3a*4 - 4*4

= 9a^2 - 24a - 16

= 3a*3a - 2*3a*4 - 4*4

= 9a^2 - 24a - 16

Added 11/21/2014 7:24:44 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [11/22/2014 2:15:49 AM]

34,588,184

questions answered

There are no comments.